2018
DOI: 10.1016/j.envint.2018.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and spatial distribution of chemical contaminants in edible fish species collected from UK and proximate marine waters

Abstract: The occurrence of a range of regulated and emerging organic environmental contaminants was investigated in 182 samples of edible marine fish sampled mainly from UK marine regions, but extending northerly to the coast of Norway and south to the Algarve. These species (sprats, mackerel, turbot, halibut, herring, grey mullet, sea bass, grey mullet, sardines, etc.) are among those considered to be at the highest risk of contamination with regulated contaminants such as polychlorinated dibenzo-p-dioxins and dibenzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 27 publications
5
24
0
1
Order By: Relevance
“…The BDE profiles from 2015-17 are similar to those found in the same population of grey seals from the late 1990s and in 2008 (Kalantzi, Hall, Thomas, & Jones, 2005;Vanden Berghe et al, 2012), found in the blubber from grey seals elsewhere (Ikonomou & Addison, 2008), and reported in recent studies on other marine mammals (Bjurlid, Dam, et al, 2018;Ochiai et al, 2017;Ramu, Kajiwara, Tanabe, Lam, & Jefferson, 2005;Rigét et al, 2006;Ross et al, 2013;Weijs, Dirtu, et al, 2009) of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationssupporting
confidence: 81%
See 1 more Smart Citation
“…The BDE profiles from 2015-17 are similar to those found in the same population of grey seals from the late 1990s and in 2008 (Kalantzi, Hall, Thomas, & Jones, 2005;Vanden Berghe et al, 2012), found in the blubber from grey seals elsewhere (Ikonomou & Addison, 2008), and reported in recent studies on other marine mammals (Bjurlid, Dam, et al, 2018;Ochiai et al, 2017;Ramu, Kajiwara, Tanabe, Lam, & Jefferson, 2005;Rigét et al, 2006;Ross et al, 2013;Weijs, Dirtu, et al, 2009) of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationssupporting
confidence: 81%
“…Recent BDE values here are 10-20-fold lower than the levels reported in adult harbour seals from the North Sea from 1999 to 2004 (Weijs, Dirtu, et al, 2009), and are an order of magnitude lower than values reported in UK grey seal pup blubber from 1998 to 2000 (Kalantzi et al, 2005), and in Salish Sea harbour seal pup blubber from 1984 to 2009 (Ross et al, 2013). Findings from other studies in the marine environment globally suggest that BDE levels peaked in the early 2000s and then fell, as a result of the ban on penta-and tetra-mixes of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationsmentioning
confidence: 67%
“…The raw data from the PCN study is very large and has been presented in a sponsor report (Fernandes et al, 2015). Raw data from the mitten crab study is provided in the supplementary information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…The principle food groups were eggs, processed meats, poultry and carcase meats, milk and dairy products, offals, and shellfish, processed foods (of vegetable origin) and others including fruit, vegetable and bread. The fish samples that were included were all sourced from UK and proximate marine waters (Fernandes et al, 2015b). The animal feeds were mainly fish feeds, compound feeds for dairy, cattle, sheep, poultry and pigs, oilseeds, legumes, grasses, cereals and cereal by-products.…”
Section: Samplingmentioning
confidence: 99%